FEASIBILITY STUDIES OF CONVERTING A MECHANISM INTO A DUALOUTPUT PULSATING STATOR-LESS MOTOR - MUSHTAQ, SHAHRYAR (2016)
This thesis is about the feasibility studies of converting a mechanism consisting of two concentric rotors into a dual-output pulsating stator-less motor. The rotors are meshed into each other, wherein the blade ofthe first rotor comprises ofelectromagnets while the blade of the second rotor comprises of permanent magnets. Each rotor is connected to its own shaft installed with an overrunning clutch which allows both rotors to rotate only in a single direction. The motor was designed, fabricated and tested. The types ofcircuits to be used was analyzed and it was concluded to be a series connection circuit. AC current was supplied to the electromagnets through slip rings. The effect of changing electric current frequencies on the performance of the motor was studied. Several frequencies of current in the range of 1 Hz to 60 Hz were tested in the experiment. When the switching of current frequency is low, the rotors tend to collide with each other resulting in loss ofenergy. Whereas, the high switching frequency will result in the retardation ofmotion, also leading to loss ofenergy.